Physiological responses and cycle characteristics during double-poling versus diagonal-stride roller-skiing in junior cross-country skiers - Andersson, E. P.; Hämberg, I.; Do Nascimento Salvador, P. C.; McGawley, K. (European Journal of Applied Physiology, 2021)
Purpose: This study aimed to compare physiological factors and cycle characteristics during cross-country (XC) roller-skiing at matched inclines and speeds using the double-poling (DP) and diagonal-stride (DS) sub-techniques in junior female and male XC skiers.